PERCEPTIONS AND LIPID PROFILES OF MIXED HERBAL DRINK (GARLIC, GINGER, LEMON, HONEY, AND APPLE VINEGAR) CONSUMERS WITH HYPERCHOLESTEROLEMIA - Ahmad Muthi Abdillah; Ahmad Sulaeman; Tiurma Sinaga (Universitas Airlangga, 2020)
Cholesterol-lowering herbal treatment made from natural ingredients are believed to be able to replace modern medicine even though it has not been scientifi cally proven. Purpose of this study was to test perceptions of customers and eff ects of mixed herbal drink on lipid profi le of consumers with hypercholesterolemia. Study was conducted using cross sectional study design consisted of three stages, that is survey, questionnaire data collection, and medical record data collection. The research subjects were selected by stratifi ed random sampling, which subjects were consumers of mixed herbal drink in total of 55 people, both men and women. Data was collected through interviews of questionnaires covering subject characteristics, subject perceptions of mixed herbal drink, and their medical record data before and after consumption of mixed herbal drinks. Paired T-test were used to observe the diff erences in subject lipid profi le before and after consumption of mixed herbal drink. Consumer perceptions toward health aspects showed that 83.7% of subjects experienced a decrease in cholesterol after consuming mixed herbal drink. Consumer emotional perception showed that 90.9% of subjects feel healthier and fi lter after consuming mixed herbal drink. Results of subject medical records on lipid profi le showed a decrease in total cholesterol, LDL, and triglycerides (p<0.05). Based on perceptions and medical records, it is known that mixed herbal drink can be used as an alternative to traditional cholesterol-lowering medicines.